2013
DOI: 10.3389/fneur.2013.00212
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Disease Correlates with Lexical Retrieval Deficits in Primary Progressive Aphasia

Abstract: Objective: To relate fractional anisotropy (FA) changes associated with the semantic and logopenic variants of primary progressive aphasia (PPA) to measures of lexical retrieval.Methods: We collected neuropsychological testing, volumetric magnetic resonance imaging, and diffusion-weighted imaging on semantic variant PPA (svPPA) (n = 11) and logopenic variant PPA (lvPPA) (n = 13) patients diagnosed using published criteria. We also acquired neuroimaging data on a group of demographically comparable healthy seni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In keeping with this, there were diffuse white matter abnormalities that were also maximal in the posterior temporal and inferior parietal white matter (Mandelli et al, 2014). The posterior temporal and inferior parietal regions involved in the present study have been linked to phonological loop functions (Gorno-Tempini et al, 2008), and the prominent involvement of the underlying white matter tracts, including the superior and inferior longitudinal fasciculi, likely underlie the poor repetition, naming and comprehension observed in this group (Powers et al, 2013). …”
Section: Discussionmentioning
confidence: 87%
“…In keeping with this, there were diffuse white matter abnormalities that were also maximal in the posterior temporal and inferior parietal white matter (Mandelli et al, 2014). The posterior temporal and inferior parietal regions involved in the present study have been linked to phonological loop functions (Gorno-Tempini et al, 2008), and the prominent involvement of the underlying white matter tracts, including the superior and inferior longitudinal fasciculi, likely underlie the poor repetition, naming and comprehension observed in this group (Powers et al, 2013). …”
Section: Discussionmentioning
confidence: 87%
“…For example proton magnetic resonance spectroscopy has demonstrated that abnormalities occur in the arcuate fasciculus in PPA . Diffusion tensor imaging (DTI) studies have linked white matter changes to language impairments specific to the clinical subtypes of PPA . However, the extent to which grey and white matter degeneration occur in parallel or sequentially is not yet known in PPA.…”
Section: Discussionmentioning
confidence: 99%
“…These tracts have also been identified as being critical components of the language network [12,25,27], in particular speech production and semantic retrieval [27,28]. A recent cross-sectional study dissociated patterns of white matter change in lvPPA and svPPA [11].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, lvPPA show widespread cortical atrophy to posterior regions of the brain, predominantly affecting the left temporo-parietal junction region, while svPPA show focal change associated with the anterior temporal lobes [2,3]. However, crosssectional studies comparing white matter integrity in lvPPA and svPPA cohorts often fail to show such a distinction [11,12], likely due to wide distributed white matter changes seen in lvPPA.…”
Section: Introductionmentioning
confidence: 95%